Evaluating the Effects of In-situ Rainwater Harvesting Techniques on Soil Moisture Conservation and Grain Yield of Maize (Zea mays L.) in Fedis District, Eastern Hararghe, Ethiopia - Amisalu Milkias; Teshale Tadesse; Habtamu Zeleke (Turkish Journal of Agriculture: Food Science and Technology)
In the drier farming regions of the world, where crop production is constrained by short growing period, unpredictable and short rainfall with sporadic run-off, in-situ rainwater harvesting is vital for successful crop production. In connection to this, a study was conducted in Fedis district of Oromia region during the main rainy seasons of 2015 and 2016 to evaluate the eﬀects of in-situ rainwater harvesting techniques (Ridge Furrow (RF), Contour Ridge (CR), and Tied Ridge (TR)) on soil moisture conservation and grain yield of maize. A spilt-plot design was used and soil moisture content was measured at three growth stages of the crop to a depth of 60 cm with 20 cm interval. The results showed that water harvesting techniques significantly increased moisture conservation compared to the control, which was flat bed preparation. Averaged over the three stages, the TR, CR and RF treatments increased soil moisture storage by 134.59, 128.57, and 121.87%, respectively, compared to the control. The study also revealed that the in-situ rainwater harvesting techniques, due to the improved soil moisture storage, significantly affected grain yield of the maize. Averaged over the two years, the TR, CR, and FR increased the grain yield 143.14, 131.47 and 121.16%, respectively, over the control treatment. Therefore, in drier environments, such as Fedis, in-situ rainwater harvesting techniques can be recommended for better moisture conservation and subsequent improvement in crop production.